Negative electrode material as well as preparation method and application thereof
By forming a gel functional layer obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, initiator and metal salt on the surface of the negative electrode sheet of an all-solid state battery, the problem of poor contact between the electrolyte and the negative electrode is solved, and the lithium dendrites are suppressed Formulate to improve the electrochemical performance and service life of the battery.
Patent Information
- Application Number
- CN202411682988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The contact between the electrolyte and the negative electrode solid interface of the all-solid state battery is poor, resulting in uneven current distribution, and lithium ions are deposited at the interface to form lithium dendrites, which in turn leads to a short circuit of the battery and affects the service life.
A gel functional layer is formed on the surface of the negative electrode sheet, and a gel layer containing a metal salt is formed by ring-opening polymerization reaction of an oxygen-containing heterocyclic monomer, an initiator and a metal salt. This gel layer acts as a buffer layer to reduce the voids at the interface, reduce the risk of lithium ion deposition, and react with lithium with metal salt to form lithium magnesium alloy and lithium fluoride, reducing the nucleation overpotential of lithium and improving conductivity.
Effectively inhibit the formation of lithium dendrites, improve the uniformity of current distribution, and improve the electrochemical performance, cyclic performance and service life of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material, a preparation method thereof and an application thereof. Background Art
[0002] With the increasing development of electric vehicles and portable electronic devices, people have higher and higher requirements for the performance of battery systems. Traditional organic liquid electrolytes are volatile and flammable, and are prone to safety problems such as combustion and explosion when the battery is overcharged or over-discharged. Solid-state batteries using solid electrolytes such as sulfides and oxides have better safety performance, a wider operating temperature range and higher energy density, and have received widespread attention.
[0003] However, the solid-solid interface contact between the electrolyte and the negative electrode of the all-solid-state battery is poor, and there are gaps at the interface, which leads to uneven current distribution. Lithium ions are easily deposited at the interface, forming lithium dendrites that pierce the electrolyte, eventually causing the battery to short circuit and affect the battery life. Summary of the invention
[0004] In view of this, the present invention provides a negative electrode material, a preparation method thereof and an application thereof. The negative electrode material provided in the present application has a functional layer on its surface, which can inhibit lithium dendrites and improve the electrochemical performance, cycle performance and service life of the battery when preparing an all-solid-state battery.
[0005] The present application provides a negative electrode material, comprising: Negative electrode; A gel functional layer is formed on at least one surface of the negative electrode plate, and the gel functional layer is obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, an initiator and a metal salt.
[0006] In some specific implementations, the oxygen-containing heterocyclic monomer is selected from at least one of tetrahydrofuran, 1,3-dioxolane, propylene carbonate, ethylene oxide or ethylene carbonate, preferably 1,3-dioxolane.
[0007] In some specific implementations, the initiator is selected from at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate or iron trifluoromethanesulfonate.
[0008] In some specific implementations, the metal salt is selected from at least one of MgF2, Mg3N2, GaN, AlN, MgI2 or AlI3.
[0009] In some specific implementations, the content of the initiator accounts for 1% to 15% of the mass of the oxygen-containing heterocyclic monomer; The content of the metal salt accounts for 0.1% to 10% of the mass of the oxygen-containing heterocyclic monomer.
[0010] In some specific implementations, the negative electrode plate is selected from a lithium plate or a silver-carbon negative electrode plate.
[0011] The present application also provides a method for preparing the above-mentioned negative electrode material, comprising the steps of: mixing an oxygen-containing heterocyclic monomer, an initiator and a metal salt to obtain a mixed solution; The mixed solution is coated on at least one surface of a negative electrode plate, and after standing to react, a gel functional layer is formed on the negative electrode plate to obtain a negative electrode material.
[0012] In some specific implementations, the static reaction time is 3h~8h; the static reaction temperature is room temperature.
[0013] The present application also provides an all-solid-state battery, comprising the negative electrode material described in the above technical solution.
[0014] In some specific implementations, the solid electrolyte in the all-solid-state battery is a sulfide solid electrolyte.
[0015] In some specific implementations, the sulfide solid electrolyte is selected from Li 3.25 Ge 0.25 P 0.7 S4, Li 10 GeP2S 12 or at least one of Li6PS5X; In Li6PS5X, X is Cl, Br or I.
[0016] The negative electrode material provided by the present application includes: a negative electrode plate; a gel functional layer formed on at least one surface of the negative electrode plate, wherein the gel functional layer is obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, an initiator and a metal salt. The present application uses an oxygen-containing heterocyclic substance as a monomer, adds a metal salt, and initiates ring-opening polymerization of the oxygen-containing heterocyclic monomer on at least one surface of the negative electrode plate under the action of an initiator to form a gel functional layer containing a metal salt. On the one hand, the gel functional layer can be used as a buffer layer to effectively alleviate the problem of poor contact between the solid-solid interface, reduce the voids at the interface, make the current distribution uniform, and reduce the deposition of lithium ions at the interface; on the other hand, the metal salt therein can react with the lithium deposited at the interface to form substances including lithium-magnesium alloy, lithium fluoride, etc., further reducing the nucleation overpotential of lithium, and improving the high ionic conductivity of the battery, thereby avoiding the formation of lithium dendrites and improving the electrochemical performance, cycle performance and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0018] Figure 1 The cycle performance of the battery prepared in Example 2 of the present application; Figure 2 Provide an interface SEM image of a battery for Example 2 of the present application; Figure 3 The cycle performance of the battery prepared in Comparative Example 3 of this application; Figure 4 The cycle performance of the battery prepared in Comparative Example 4 of the present application. DETAILED DESCRIPTION
[0019] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0020] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0021] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0022] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0023] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0024] The present application provides a negative electrode material, comprising: Negative electrode; A gel functional layer is formed on at least one surface of the negative electrode plate, and the gel functional layer is obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, an initiator and a metal salt.
[0025] The present application uses oxygen-containing heterocyclic substances as monomers, adds metal salts, and initiates ring-opening polymerization of oxygen-containing heterocyclic monomers on at least one surface of the negative electrode plate under the action of an initiator to form a gel functional layer containing metal salts. On the one hand, the gel functional layer can be used as a buffer layer to effectively alleviate the problem of poor solid-solid interface contact, reduce the gaps at the interface, make the current distribution uniform, and reduce the deposition of lithium ions at the interface; on the other hand, the metal salts therein can react with the lithium deposited at the interface to form substances including lithium-magnesium alloys and lithium fluoride, further reducing the nucleation overpotential of lithium, and improving the high ion conductivity of the battery, thereby avoiding the formation of lithium dendrites and improving the electrochemical performance and service life of the battery.
[0026] The negative electrode material provided in the present application includes a negative electrode sheet, and the negative electrode sheet is preferably a negative electrode sheet containing metallic lithium, including but not limited to a metallic lithium sheet, a silver-carbon negative electrode sheet, etc., preferably a silver-carbon negative electrode sheet. The present application has no special restrictions on the thickness, size, etc. of the negative electrode sheet, and those skilled in the art can select as needed.
[0027] A gel functional layer is formed on at least one surface of the negative electrode material provided in the present application, and the gel functional layer is obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, an initiator and a metal salt. Specifically, the gel functional layer is a gel layer formed by ring-opening polymerization of an oxygen-containing heterocyclic monomer initiated by an initiator, and the gel layer contains a metal salt. The gel layer is flexible and can be used as a buffer layer to alleviate the problem of poor solid-solid interface contact, and the metal salt can react with the lithium deposited at the interface to form a layer including lithium-magnesium alloy, lithium fluoride and other substances. The lithium fluoride layer formed in situ can increase the diffusion rate of lithium ions during subsequent cycles and accelerate the migration of lithium to the negative electrode side. The lithium-magnesium alloy layer formed in situ can reduce the nucleation overpotential of lithium, accelerate the deposition of lithium, and avoid the formation of lithium dendrites at the interface. Therefore, the gel functional layer can not only inhibit lithium dendrites, but the LiF and LiMg alloys contained at the interface can also accelerate the transmission of lithium and prevent the formation of subsequent lithium dendrites.
[0028] In some specific implementations, the oxygen-containing heterocyclic monomer includes but is not limited to tetrahydrofuran, 1,3-dioxolane, propylene carbonate, ethylene oxide or vinyl carbonate, and can be one or more thereof. When the oxygen-containing heterocyclic monomer is a combination of multiple substances, the present application does not have any special restrictions on the content of each specific substance. In some embodiments, the oxygen-containing heterocyclic monomer is preferably 1,3-dioxolane, which undergoes ring-opening polymerization under the action of an initiator to obtain a polymer gel.
[0029] In some specific implementations, the initiator includes but is not limited to lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium tetrafluoroborate (LiBF4) or iron trifluoromethanesulfonate [Fe(OTf)3], which can be one or more thereof. When the initiator is a combination of multiple substances, the present application does not have any special restrictions on the content of each specific substance. In some embodiments, the initiator is preferably lithium difluorooxalate borate (LiDFOB). In some specific implementations, the content of the initiator accounts for 1% to 15% of the mass of the oxygen-containing heterocyclic monomer, preferably 1.5% to 12%, and more preferably 2% to 10%.
[0030] In some specific implementations, the metal salt includes but is not limited to MgF2, Mg3N2, GaN, AlN, MgI2 or AlI3, which can be one or more thereof. When the metal salt is a combination of multiple substances, the present application has no special restrictions on the content of each specific substance. In some embodiments, the metal salt is preferably MgF2. In some specific implementations, the content of the metal salt accounts for 0.1% to 10% of the mass of the oxygen-containing heterocyclic monomer, preferably 0.5% to 8%, and more preferably 1% to 5%.
[0031] The present application also provides a method for preparing the above-mentioned negative electrode material, comprising the steps of: mixing an oxygen-containing heterocyclic monomer, an initiator and a metal salt to obtain a mixed solution; The mixed solution is coated on at least one surface of a negative electrode plate, and after standing to react, a gel functional layer is formed on the negative electrode plate to obtain a negative electrode material.
[0032] The present application first mixes an oxygen-containing heterocyclic monomer, an initiator and a metal salt to obtain a mixed solution. The selection of oxygen-containing heterocyclic monomers, initiators and metal salts is described above, and the present application will not repeat them here. The present application has no special restrictions on the order of mixing the oxygen-containing heterocyclic monomer, initiator and metal salt. When the oxygen-containing heterocyclic monomer is 1,3-dioxolane, since the 1,3-dioxolane monomer is in a liquid state, the initiator and the metal salt are preferably added to the 1,3-dioxolane monomer, and more preferably, the initiator is first added and mixed evenly, and then the metal salt is added and mixed evenly to obtain a mixed solution. In some specific implementations, in the mixed solution, the concentration of the initiator is 0.1mol / L~5mol / L, more preferably 0.2mol / L~3mol / L; the mass concentration of the metal salt is 0.1%~10%, preferably 0.5%~8%.
[0033] After obtaining the mixed solution, it is applied to the surface of the negative electrode plate. After standing for reaction, a gel functional layer is formed on the negative electrode plate to obtain a negative electrode material. The present application has no special restrictions on the coating method, and it can be any method such as coating and infiltration, so that the mixed solution can react in situ on the surface of the negative electrode plate. After coating, under the condition of standing, the oxygen-containing heterocyclic monomer can undergo a ring-opening polymerization reaction under the action of the initiator to form a polymer gel, and the metal salt is present in the polymer gel. In some specific implementations, the standing reaction time is 3h~8h, preferably 4h~7h; the standing reaction temperature is room temperature. After the reaction is completed, the negative electrode material can be obtained without drying treatment.
[0034] The present application also provides an all-solid-state battery, comprising the negative electrode material described in the above technical solution. Specifically, the all-solid-state battery comprises a positive electrode, an all-solid-state electrolyte and the negative electrode material described in the above technical solution.
[0035] The all-solid-state battery includes an all-solid-state electrolyte, and the solid electrolyte in the all-solid-state battery can be an oxide solid electrolyte or a sulfide solid electrolyte, preferably a sulfide solid electrolyte. In some specific implementations, the sulfide solid electrolyte is selected from Li 3.25 Ge 0.25 P 0.7 S4, Li 10 GeP2S 12or at least one of Li6PS5X; in Li6PS5X, X is Cl, Br or I. In some specific implementations, the sulfide solid electrolyte is Li6PS5Cl.
[0036] The all-solid-state battery includes a positive electrode. The present application has no special restrictions on the positive electrode. The positive electrode material includes but is not limited to lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese oxide, etc., preferably lithium nickel cobalt manganese oxide.
[0037] The present application has no special restrictions on the preparation method of the all-solid-state battery, and it can be prepared according to methods well known to those skilled in the art.
[0038] In the all-solid-state battery provided in the present application, the gel functional layer filled between the negative electrode plate and the all-solid-state electrolyte is flexible and can fill the gaps so that lithium ions will not be deposited in the gaps, thereby effectively improving the interface contact problem; the metal salt therein can react with the lithium deposited at the interface to form a lithium fluoride layer and a lithium-magnesium alloy layer in situ, which can effectively reduce the subsequent nucleation overpotential of lithium and increase the subsequent transmission speed of lithium ions. The lithium fluoride and lithium-magnesium alloy formed in situ will automatically fill the interface gaps between the electrolyte and the negative electrode, which is beneficial to the uniform deposition of lithium, and therefore has the function of preventing and inhibiting lithium dendrites.
[0039] The experimental results show that although a single gel layer improves ionic conductivity, there is still a risk of lithium deposition at the interface between the gel layer and the negative electrode. Although a single MgF2 layer has the function of inhibiting dendrites at the interface, the formed LiF has poor toughness and still has the problem of dendrite piercing after long-term cycling. The all-solid-state battery provided by this application effectively solves the above problems and has good electrochemical performance and service life.
[0040] The negative electrode material, preparation method and application thereof provided in the present application are further described below in conjunction with embodiments.
[0041] Example 1 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.5 mol / L; MgF2 accounting for 1% of the mass of DOL was added to the glass bottle and stirred evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The silver-carbon negative electrode disc was placed in a glove box and allowed to stand for 4 hours to allow DOL to undergo ring-opening polymerization under the action of LiDFOB, forming a polymer gel layer 8 μm thick on the surface of the negative electrode. (3) Using the ternary positive electrode material nickel cobalt manganese (NCM811) as the positive electrode active material, C45 as the conductive agent, sulfide solid electrolyte Li6PS5Cl as the electrolyte, and 6% polyisobutylene-p-xylene as the binder, the active material: conductive agent: electrolyte: binder = 85:2:10:3 are mixed evenly to prepare a positive electrode slurry, which is then coated on the electrode to obtain a positive electrode sheet.
[0042] (4) Using sulfide solid electrolyte Li6PS5Cl as the electrolyte, weigh 100 mg of electrolyte powder and put it into the mold battery, and use 600 MPa to press the tablet to obtain a solid electrolyte sheet.
[0043] (5) The negative electrode sheet prepared in step (2) is used as the negative electrode, the positive electrode sheet prepared in step (3) is used as the positive electrode, and the solid electrolyte sheet prepared in step (4) is assembled into a mold battery in the order of positive electrode sheet / solid electrolyte sheet / negative electrode sheet, and the electrochemical performance test is performed. During the cycle test, the charge and discharge are performed at 0.05C. The results are shown in Table 1, which shows the performance test results of the batteries provided in the examples and comparative examples of the present application.
[0044] Example 2 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.5 mol / L; MgF2 accounting for 2% of the mass of DOL was added to the glass bottle and stirred evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The silver-carbon negative electrode disc was placed in a glove box and allowed to stand for 4 hours to allow DOL to undergo ring-opening polymerization under the action of LiDFOB, forming a polymer gel layer 8 μm thick on the surface of the negative electrode. (3) Using ternary positive electrode material nickel cobalt manganese (NCM811) as positive electrode active material, C45 as conductive agent, sulfide solid electrolyte Li6PS5Cl as electrolyte, and 6% polyisobutylene-p-xylene as binder, the active material: conductive agent: electrolyte: binder = 85:2:10:3 are mixed evenly to prepare positive electrode slurry, and then coated on the electrode to obtain a positive electrode sheet; (4) Using sulfide solid electrolyte Li6PS5Cl as the electrolyte, weigh 100 mg of electrolyte powder and put it into the mold battery, and use 600 MPa to press the tablet to obtain a solid electrolyte sheet.
[0045] (5) The negative electrode sheet prepared in step (2) is used as the negative electrode, the positive electrode sheet prepared in step (3) is used as the positive electrode, and the solid electrolyte sheet prepared in step (4) is assembled into a mold battery in the order of positive electrode sheet / solid electrolyte sheet / negative electrode sheet, and the electrochemical performance test is carried out. During the cycle test, the charge and discharge are carried out at 0.05C. The results are shown in Figure 1 and Table 1, Figure 1 The cycle performance of the battery prepared in Example 2 of the present application is shown in Table 1. The performance test results of the batteries provided in the examples and comparative examples of the present application are shown in Table 1.
[0046] After disassembling the battery prepared in step (5), the morphology of its cross section was characterized. The results are shown in Figure 2 , Figure 2 The interface SEM image of the battery provided in Example 2 of the present application shows the electrolyte, the MgF2 gel functional layer and the silver-carbon negative electrode from top to bottom. Figure 2 It can be seen that the MgF2 gel functional layer promotes good contact between the silver-carbon negative electrode and the electrolyte, and effectively avoids the generation of gaps between the negative electrode and the electrolyte.
[0047] Example 3 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.5 mol / L; MgF2 accounting for 5% of the mass of DOL was added to the glass bottle and stirred evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The silver-carbon negative electrode disc was placed in a glove box and allowed to stand for 4 hours to allow DOL to undergo ring-opening polymerization under the action of LiDFOB, forming a polymer gel layer 8 μm thick on the surface of the negative electrode. (3) Using the ternary positive electrode material nickel cobalt manganese (NCM811) as the positive electrode active material, C45 as the conductive agent, sulfide solid electrolyte Li6PS5Cl as the electrolyte, and 6% polyisobutylene-p-xylene as the binder, the active material: conductive agent: electrolyte: binder = 85:2:10:3 are mixed evenly to prepare a positive electrode slurry, which is then coated on the electrode to obtain a positive electrode sheet.
[0048] (4) Using sulfide solid electrolyte Li6PS5Cl as the electrolyte, weigh 100 mg of electrolyte powder and put it into the mold battery, and use 600 MPa to press the tablet to obtain a solid electrolyte sheet.
[0049] (5) The negative electrode sheet prepared in step (2) is used as the negative electrode, the positive electrode sheet prepared in step (3) is used as the positive electrode, and the solid electrolyte sheet prepared in step (4) is assembled into a battery in the order of positive electrode sheet / solid electrolyte sheet / negative electrode sheet, and an electrochemical performance test is performed. During the cycle test, charge and discharge are performed at 0.05C. The results are shown in Table 1, which shows the performance test results of the batteries provided in the examples and comparative examples of the present application.
[0050] Comparative Example 1 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.3 mol / L; MgF2 accounting for 2% of the mass of DOL was added to the glass bottle and stirred evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The DOL was placed on a silver-carbon negative electrode disc and left in a glove box for 4 hours. The DOL was in a solution state and failed to polymerize, indicating that the concentration of the initiator LiDFOB was too low and failed to initiate the ring-opening polymerization of DOL.
[0051] Comparative Example 2 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.4 mol / L; MgF2 accounting for 2% of the mass of DOL was added to the glass bottle and stirred evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The DOL was placed on a silver-carbon negative electrode disc and left in a glove box for 4 hours. The DOL was still in a solution state and was not completely polymerized, indicating that the concentration of the initiator LiDFOB was too low and failed to initiate the ring-opening polymerization of DOL.
[0052] Comparative Example 3 (1) lithium difluorooxalatoborate (LiDFOB) and 1,3-dioxolane (DOL) were mixed evenly in a glass bottle to make the concentration of LiDFOB 0.5 mol / L to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 The silver-carbon negative electrode disc was placed in a glove box and allowed to stand for 4 hours to allow DOL to undergo ring-opening polymerization under the action of LiDFOB, forming a polymer gel layer 8 μm thick on the surface of the negative electrode. (3) Using the ternary positive electrode material nickel cobalt manganese (NCM811) as the positive electrode active material, C45 as the conductive agent, sulfide solid electrolyte Li6PS5Cl as the electrolyte, and 6% polyisobutylene-p-xylene as the binder, the active material: conductive agent: electrolyte: binder = 85:2:10:3 are mixed evenly to prepare a positive electrode slurry, which is then coated on the electrode to obtain a positive electrode sheet.
[0053] (4) Using sulfide solid electrolyte Li6PS5Cl as the electrolyte, weigh 100 mg of electrolyte powder and put it into the mold battery, and use 600 MPa to press the tablet to obtain a solid electrolyte sheet.
[0054] (5) The negative electrode sheet prepared in step (2) is used as the negative electrode, the positive electrode sheet prepared in step (3) is used as the positive electrode, and the solid electrolyte sheet prepared in step (4) is assembled into a mold battery in the order of positive electrode sheet / solid electrolyte sheet / negative electrode sheet, and the electrochemical performance test is carried out. During the cycle test, the charge and discharge are carried out at 0.05C. The results are shown in Figure 3 and Table 1, Figure 3 The cycle performance of the battery prepared in comparative example 3 of the present application is shown in Table 1. The performance test results of the batteries provided in the embodiments and comparative examples of the present application are shown in Table 1.
[0055] Comparative Example 4 (1) Mix MgF2 and 1,3-dioxolane (DOL) in a glass bottle so that MgF2 accounts for 2% of the mass of DOL, and stir evenly to obtain a mixed solution; (2) Take 2 mL of the mixed solution obtained in step (1) and apply it on a surface with a diameter of 1 cm and an area of 0.785 cm 2 On the silver-carbon negative electrode disc, a MgF2 modification layer is formed on the surface of the negative electrode after natural drying; (3) Using the ternary positive electrode material nickel cobalt manganese (NCM811) as the positive electrode active material, C45 as the conductive agent, sulfide solid electrolyte Li6PS5Cl as the electrolyte, and 6% polyisobutylene-p-xylene as the binder, the active material: conductive agent: electrolyte: binder = 85:2:10:3 are mixed evenly to prepare a positive electrode slurry, which is then coated on the electrode to obtain a positive electrode sheet.
[0056] (4) Using sulfide solid electrolyte Li6PS5Cl as the electrolyte, weigh 100 mg of electrolyte powder and put it into the mold battery, and use 600 MPa to press the tablet to obtain a solid electrolyte sheet.
[0057] (5) The negative electrode sheet prepared in step (2) is used as the negative electrode, the positive electrode sheet prepared in step (3) is used as the positive electrode, and the solid electrolyte sheet prepared in step (4) is assembled into a battery in the order of positive electrode sheet / solid electrolyte sheet / negative electrode sheet, and the electrochemical performance test is carried out. During the cycle test, the charge and discharge are carried out at 0.05C. The results are shown in Figure 4 and Table 1, Figure 4 The cycle performance of the battery prepared in comparative example 4 of the present application is shown in Table 1. The performance test results of the batteries provided in the embodiments and comparative examples of the present application are shown in Table 1.
[0058] Table 1 Performance test results of the batteries provided in the examples and comparative examples of the present application
[0059] It can be seen from Table 1 that after 20 cycles, the discharge specific capacity and discharge specific capacity retention rate of the battery prepared in Example are higher than those of Comparative Example 3 and Comparative Example 4. The battery provided in the present application has good electrochemical properties.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode material comprising: Negative electrode; A gel functional layer is formed on at least one surface of the negative electrode plate, and the gel functional layer is obtained by ring-opening polymerization of an oxygen-containing heterocyclic monomer, an initiator and a metal salt.
2. The negative electrode material according to claim 1, characterized in that The oxygen-containing heterocyclic monomer is selected from at least one of tetrahydrofuran, 1,3-dioxolane, propylene carbonate, ethylene oxide or ethylene carbonate.
3. The negative electrode material according to claim 1, characterized in that The initiator is selected from at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate or iron trifluoromethanesulfonate.
4. The negative electrode material according to claim 1, characterized in that The metal salt is selected from at least one of MgF2, Mg3N2, GaN, AlN, MgI2 or AlI3.
5. The negative electrode material according to claim 3, characterized in that The content of the initiator accounts for 1% to 15% of the mass of the oxygen-containing heterocyclic monomer; The content of the metal salt accounts for 0.1% to 10% of the mass of the oxygen-containing heterocyclic monomer.
6. The negative electrode material according to claim 3, characterized in that The negative electrode plate is selected from a lithium plate or a silver-carbon negative electrode plate.
7. The method for preparing the negative electrode material according to any one of claims 1 to 6, characterized in that: Includes steps: mixing an oxygen-containing heterocyclic monomer, an initiator and a metal salt to obtain a mixed solution; The mixed solution is coated on at least one surface of a negative electrode plate, and after standing to react, a gel functional layer is formed on the negative electrode plate to obtain a negative electrode material.
8. The preparation method according to claim 7, characterized in that: The standing reaction time is 3h~8h; the standing reaction temperature is room temperature.
9. An all-solid-state battery comprising the negative electrode material according to any one of claims 1 to 6.
10. The all-solid-state battery according to claim 9, characterized in that: Its solid electrolyte is a sulfide solid electrolyte.
11. The all-solid-state battery according to claim 10, characterized in that: The sulfide solid electrolyte is selected from Li 3.25 Ge 0.25 P 0.7 S4, Li 10 GeP2S 12 or at least one of Li6PS5X; In Li6PS5X, X is Cl, Br or I.